(untitled) (Jurnal Hortikultura Indonesia, 2023)
Katuk is vegetables which can fulfil human nutritional needs. Plants experiencing water stress require additional nutrients in the growth process, namely by means of fertilization. The study aimed to determine the effect of water stress and foliar fertilization interval on the growth of katuk plants. The experimental design used was a split-plot design in a completely randomized group design (RKLT) consisting of 2 factors: leaf fertilization interval as the main plot and water stress as a subplot. The foliar fertilization interval consisted of 3 levels, namely P0 (without fertilization), P1 (2 weeks), and P2 (4 weeks). The water stress factor consists of 4 levels, namely C1 (40% field capacity (KL)), C2 (60% KL), C3 (80% KL), and C4 (100% KL). The study was conducted with three replications obtained from 12 combinations so that there were 36 experimental units. Water stress did not significantly affect the growth of katuk plants. The growth of plants that received a reduction in water supply of up to 40 field capacity was still equivalent to plants with water supply of up to field capacity (100%). The time of foliar fertilization had a significant effect on the parameters of the number of branches, number of leaves, and harvest weight at intervals of 2 and 4 weeks. The interaction between water stress and foliar fertilization did not affect the growth of katuk plants. Keywords: effect, nutrients, nutrition, parameters, vegetables